Agency and argument realization in early child Inuktitut - Notaker, Nikolai (The University of Edinburgh, 2010)
Argument realization, and particularly argument omission, is a subject that has been widely studied in the field of child language research, and several different theories have been put forth to explain this phenomenon. In this study, semantic agency is proposed as a contributing factor. To test this, corpus data of four children acquiring Inuktitut were coded for agency on the grammatical subjects produced by the children. Statistical analyses were performed to assess the relationship between subject argument form and agency. A qualitative analysis of the verb semantics associated with non-agent subjects was also performed. While the analyses yielded some statistically significant results, no clear relationship between these factors could be identified. The qualitative analysis, on the other hand, did appear to reveal a weak trend in terms of a relationship between verb semantics and argument realization. The findings are discussed in terms of the broader aspects of the development of agency, transitivity, and ergativity.